Concerted Collusion: Studying Multiagency Institutional Cover-Up - Montgomery, Anthony (Frontiers in Psychology, 2022)
Many important organizational events do not lend themselves easily to experimental manipulation, and thus, one can only study them retrospectively by combining the investigative tools provided by both the social sciences and humanities. A cover-up, meaning an attempt to prevent the public from discovering information about a serious crime or mistake, is such a phenomenon. The objective of the present paper is to develop an initial taxonomy of how organizational researchers can study what happens when multiple organizations and institutions conspire to cover-up the causes of a tragedy. For this purpose, the 1989 United Kingdom Hillsborough tragedy and the 27 year cover-up will be analyzed. Hillsborough is the best (and worst) example of a cover-up, in that the objective facts were known from early on but the subjective elements (i.e., attitudes, bias, and collusion) resulted in a 27 year search for justice for the victims. It deserves special attention as an example of multiagency institutional cover-up, in that the range and diversity of institutional actors pitted against the victims grossly outweighed them in terms of material resources, social power (in terms of social class differences), and the ability to control the narrative of the tragedy. Using a thematic analysis approach, five main themes were identified as: (1) Unwilling, but compliant, participants who are unlikely to be whistleblowers, (2) Suppressing/withholding important information, (3) Proactively engaging the support of related actors/institutions that helps create a critical mass, (4) Owning the narrative, and (5) Moral disengagement.